Políticas públicas de incentivo ao inventor independente e sua importância no cenário da propriedade intelectual em universidades brasileiras - Bruno de Souza Leite Thiebaut (2016)
This dissertation will analyze the public policy of encouraging independent inventors, their importance in the scenario of the national intellectual property and its interaction with universities. Public incentives for independent inventors will be presented in order to improve the rate of innovation in the country, the adoption of inventions in Brazilian universities and the further consequences of this insertion, the advantages or disadvantages of this procedure in the innovation law and considerations about whether independent inventions cause some impact on the Brazilian innovation system.